Competence of the European Union to Decide on Judicial Appointments in Poland - Harasimowicz, Karolina (Polish Review of International and European Law, 2022)
A member state of the European Union (EU) cannot function within the EU network of legal regulations if it rejects the principle of cooperation based on the impartiality of the courts. This principle subscribes to the EU standards of the rule of law and mutual trust and cooperation with the Court of Justice of the European Union. In November 2019, it received judicial recognition when the Court laid down the characteristics of an unbiased court within the EU legal framework. Thus, it is imperative for member states, which includes Poland, to recognise this principle and ensure its application in their domestic legal structure. They have to acknowledge that the EU is still a supranational network of regulation, economics, and values